Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{3}{2}-\left(x-\frac{7}{3}\right)=\left|-\frac{3}{4}-\frac{9}{8}\right|\)
=> \(\frac{3}{2}-x+\frac{7}{3}=\left|-\frac{15}{8}\right|\)
=> \(\frac{3}{2}-x+\frac{7}{3}=\frac{15}{8}\)
=> \(\frac{3}{2}-x=-\frac{11}{24}\)
=> \(x=\frac{47}{24}\)
b) \(\frac{5}{2}-\left(\frac{3}{2}-\frac{7}{3}+x\right)=\frac{8}{15}-\left(\frac{1}{4}-\frac{7}{10}\right)\)
=> \(\frac{5}{2}-\frac{3}{2}+\frac{7}{3}-x=\frac{8}{15}-\left(-\frac{9}{20}\right)\)
=> \(\frac{10}{3}-x=\frac{59}{60}\)
=> \(x=\frac{10}{3}-\frac{59}{60}=\frac{47}{20}\)
c) \(2\left(\frac{3}{4}-5x\right)=\frac{4}{5}-3x\)
=> \(\frac{3}{2}-10x-\frac{4}{5}+3x=0\)
=> \(\left(\frac{3}{2}-\frac{4}{5}\right)+\left(-10x+3x\right)=0\)
=> \(\frac{7}{10}-7x=0\)
=> \(7x=\frac{7}{10}\)
=> x = 1/10
a. 3/5 . 15/7 - 15/7 . 8/5
= 15/7(3/5-8/5)
=15/7. -\(\frac{1}{1}\)
=22/7
b. 4/5 . 1 3/7 + 4/5 . 4/7
=4/5(13/7+4/7)
=4/5.17/7
= 68/35
\(\left(2x-15\right)^5=\left(2x-15\right)^3\)
\(\Rightarrow\orbr{\begin{cases}2x-15=1\\2x-15=-1\end{cases}}\)Hoặc 2x - 15 = 0
<=> x = 8 hoặc x = 7 hoặc x = 15/2
Ơ chị k5 mà ạ ?
5/17 + -4/9 + -20/31 + -11/31 < x < -3/7 + 7/15 + 4/-7 + 8/15 + 2/3
-175/153<x\(\le\)2/3
-175/153<x\(\le\)102/153
suy ra -175<x\(\le\)153
vậy x bằng (-174/153,-173/153,-172/153,.........,101/153,102/153
\(1,x.\left(x+7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x+7=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}}\)
\(2,\left(x+12\right).\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+12=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-12\\x=3\end{cases}}}\)
\(3,\left(-x+5\right).\left(3-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}-x+5=0\\3-x=0\end{cases}\Rightarrow\orbr{\begin{cases}-x=-5\\x=3\end{cases}\Rightarrow}\orbr{\begin{cases}x=5\\x=3\end{cases}}}\)
\(4,24:\left(3x-2\right)=-3\)
\(3x-2=-8\)
\(3x=-6\)
\(x=-2\)
\(5,-45:5\left(-3-2x\right)=3\)
\(5\left(-3-2x\right)=-15\)
\(-3-2x=-3\)
\(2x=0\)
\(x=0\)
\(6,x.\left(2+x\right)\left(7-x\right)=0\)
\(x=0\) hoặc \(\orbr{\begin{cases}2+x=0\\7-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-2\\x=7\end{cases}}}\)
\(7,\left(x-1\right)\left(x+2\right)\left(-x+3\right)=0\)
TH1: x-1=0 TH2 : x+2=0 TH3: -x+3=0
x=1 x=-2 -x=-3 => x=3
\(\left(5\frac{4}{9}+x-7\frac{7}{18}\right):15\frac{3}{4}=0\)
\(\Leftrightarrow\left(\frac{49}{9}+x-\frac{133}{18}\right)=\frac{4}{63}\)
\(\Leftrightarrow\frac{98-133}{18}+x=\frac{4}{63}\)
\(\Leftrightarrow-\frac{35}{18}+x=\frac{4}{63}\)
\(\Leftrightarrow x=\frac{4}{63}+\frac{35}{18}=\frac{253}{126}\)